Analisis Fundamental Makro, Karakteristik Perusahaan, Terhadap Nilai Perusahaan Dengan Struktur Kepemilikan, Manajemen Laba, Kinerja Keuangan Sebagai Variabel Intervening Pada Perusahaan Manufaktur Tahun 2019-2023 - Diah Indri Anggriyanti; Hwihanus Hwihanus (Akuntansi, 2024)
In the current era, it is an era of rapid development in the industrial world so that it can create competition, namely for investors and companies. For a good picture for the company, especially by having a sense of trust so as to attract the attention of investors to invest in the company. For this reason, for economic development in the company must have the ability or good performance compared to its competitors. As for the benefits for investors, this research provides information about the factors that affect the value of a company to help investors in making investment decisions. For companies, researchers want to provide information about factors that can increase company value (Y) so that companies can develop the right strategy to increase company value and generate investment interest. Therefore, researchers have the aim of wanting to analyze how the influence of Macro Fundamentals (X1), Company Characteristics (X2) with Ownership Structure (Z1), Earnings Management (Z2), and Financial Performance (Z3) on Company Value (Y) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in Indonesia in the period 2019 to 2023. The most dominant intervening variable in connecting macro fundamentals, company characteristics, ownership structure, and firm value is financial performance. This concludes that financial performance is an important factor linking macro fundamentals, firm characteristics, ownership structure, and firm value. The findings of this study have important implications for investors, corporate managers, and policy makers. Therefore, the research method used is a quantitative approach that utilizes secondary data derived from financial statement information and economic data published on the internet, specifically the Indonesia Stock Exchange (IDX). The data was processed using the Partial Least Square (Smart PLS 4) software application.